SENIOR HIGH SCHOOL TEACHERS’ CONCEPTIONS OF CREATIVITY IN TEACHING ENGLISH AS FOREIGN LANGUAGE - Ai Erti Susanti (EEAL Journal (English Education and Applied Linguistics Journal), 2020)
This research aims to investigate the teachers’ conception of creativity in teaching English as foreign language. This research usesd qualitative case study research since this research investigated in-depth events that investigated teachers understanding the concept of creativity in teaching English and how teachers applied the concept of creativity in teaching English. In this research data were collected from semi-structured interviews of two senior high school teachers. The data were then analyzed by following the framework from Lodico, Spaulding & Voegtle (2010). As the result, both participants had understanding the concept of creativity in learning English and both participants had many characteristics in applying creativity in their classroom such as activities that have challenges, interesting content,flexible, looking for new ways of doing things, adapting lessons, customize the lessons, uses of technology, and motivate the students.